Mechanism and Inducing Factors of Rockburst Events of Roadways Under Ultrathick Strata - Hao, Zhen; Sun, Guangzhong; Zhang, Guohua (Frontiers in Earth Science, 2022)
The overlying strata of the Yima coalfield are ultrathick conglomerate. Aiming at the problem of frequent occurrence of rockburst events in the central Yima coalfield during 2006–2015, the characteristics of rockburst events, microseismic (MS) monitoring, and rockburst event-inducing factors were analyzed through data mining and field investigation methods. The results showed that the rockburst events in roadways mainly occurred during mining of the working face, and they occurred at a large buried depth and were within the influence of mining stress, accompanied by an abrupt energy release. The occurrence of rockburst in roadways was accompanied by a sudden release of energy. The ultrathick strata and the fault nearby were the key influence factors of rockburst events. The stress field of roadway surrounding rocks was changed because of the mining disturbance, roadway repair and maintenance, and blasting, which would change the regional stress fields in the surrounding rocks and induce roadway rockburst events. The characteristics of rockburst events were floor heave, sharp convergence of two side walls, severe damage of the supporting body, and even closure of the roadway. The occurrence of rockburst can be prevented by reducing the mining speed and injecting water into coal seam.